Impact of financial toxicity on adults with cancer during the COVID-19 pandemic: an integrative review - Luciana de Alcantara Nogueira; Cristiano de Oliveira Ribeiro; Leonel dos Santos Silva; Yasmin Hiorrana dos Santos; Luciana Puchalski Kalinke (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to identify the repercussions of financial toxicity on the lives of adult cancer patients during the COVID-19 pandemic. Methods: an integrative review was conducted using the PubMed, Web of Science, Scopus, and Embase databases, as well as the Virtual Health Library portal, in March 2023. Results: out of 62 studies found, 13 were included for analysis. The primary repercussions of financial toxicity included difficulties in covering basic expenses such as food, housing, medication, transportation, and internet access; increased anxiety and concerns related to health and financial situations; reduction or absence of income; challenges in obtaining treatment or accessing healthcare services; rising expenses; and telemedicine as a less burdensome alternative. Conclusions: the pandemic has exacerbated financial toxicity; therefore, healthcare teams must recognize it as an adverse event of oncological treatment and understand its potential to affect various aspects of patients' lives.